Densities and population sizes of raptors in Uganda's conservation areas. (2nd January 2019) - Pomeroy, Derek; Kibuule, Micheal; Nalwanga, Dianah; Kaphu, George; Opige, Michael; Shaw, Phil
Abstract : Projected increases in Africa's human population over the next 40 years point to further, large-scale conversion of natural habitats into farmland, with far-reaching consequences for raptor species, some of which are now largely restricted to protected areas (PAs). To assess the importance of PAs for raptors in Uganda, we conducted an annual road survey through savanna, pastoral and agricultural land during 2008–2015. Here, we present density estimates for 34 diurnal raptor species, 17 of which were encountered largely or entirely within PAs. These included seven out of eight globally threatened or near-threatened species surveyed. Based mainly on published demographic values, we converted density estimates (birds 100 km−2) to numbers of adult pairs, for 10 resident, savanna-dependent species. We then estimated adult population sizes within conservation areas (individual PAs and clusters of contiguous PAs), based on the area of savanna in each site. This suggested that two threatened residents, Martial Eagle Polemaetus bellicosus and Lappet-faced Vulture Torgos tracheliotos, have national breeding populations of just 53–75 and 74–105 pairs, respectively. A third species, White-headed Vulture Trigonoceps occipitalis, may have a breeding population of just 22–32 pairs. In each case, at least 90% of pairs are thought to reside within Uganda's five largest conservation areas. In three cases our estimates of pair density were markedly lower than in other studies, while in six cases they were broadly consistent with published findings, often derived using more intensive survey methods. Further work is required to determine the accuracy of our estimates for individual conservation areas, and to assess the long-term viability of Uganda's threatened raptor populations.